Penerapan Model Project Based Learning pada Mata Kuliah Bisnis Digital Bagi Mahasiswa Pendidikan Biologi Universitas Tanjungpura - Wahyuni, Eko Sri; Titin, Titin; Rosanti, Melsinta; Agresi, Embun (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Digital business is a form of technology development that promotes a product or brand. At the Biology Education study program of Faculty of Teacher Training and Education Tanjungpura University, Digital Business is a course that targets to increase students’ entrepreneurship. The learning model implemented in this course is PjBL model (Project Based Learning), which is a model to give lecturer chances to manage the learning process through projects. In this research, the method used in this research is qualitative descriptive. The purpose of this research is to determine the implementation of PjBL model in Digital Business course for the students of Biology Education study program of Universitas Tanjungpura in the academic year 2022/2023. The research object are 15 Biology Education students. The research instrument were observation sheets on the implementation of the learning process and student project observation sheets. Data analysis technique used in this research is data triangulation from the observation results. Based on the research results, it is known that the implementation of PjBL model in Digital Business course for Biology Education study program students in the academic year 2022/2023 is categorized as good. The implementation of the learning process reaches 100%. Students succeeded in creating a project to market products through various digital platforms.